Cold atmospheric pressure plasma jet modulates Candida albicans virulence traits - Chiodi Borges, Aline [UNESP] (2017)
The occurrence of Candida-related infections depends on the interplay between fungal virulence factors and host's immune system. For this reason, interfering with fungal virulence is a promising approach to prevent or treat such diseases. The goal of this study was to analyze the effects of cold atmospheric pressure plasma jet operated with Helium (He-CAPPJ) on C. albicans virulence traits and biofilms. The study also aimed to evaluate the cytotoxicity and genotoxicity of He-CAPPJ to Vero cells. The effective operational parameters of He-CAPPJ against C. albicans SC 5314 were determined. Sub-inhibitory times of exposure were used to evaluate the effect of He-CAPPJ on morphogenesis (yeast-hyphae transition), adherence to epithelial cells, and exoenzymes production. Cytotoxicity to Vero cells was also assessed by MTT assay and genotoxicity was investigated by micronucleus test. A promising effect of He-CAPPJ on morphogenesis was observed, with a reduction of almost 40 times in the filamentation rate compared to the non-exposed group. He-CAPPJ was able to reduce C. albicans adherence and to decrease fungal biofilm viability. No effect on exoenzymes production was observed. In conclusion, He-CAPPJ was able to attenuate fungal adherence and morphogenesis with low cytotoxicity after short treatment times. Periods of exposure effective against biofilms were cytotoxic to Vero cells. He-CAPPJ did not show genotoxic effect. Therefore, He-CAPPJ has potential to be applied as an adjuvant in the treatment of C. albicans superficial infections.